2012
DOI: 10.1016/j.bbr.2011.10.037
|View full text |Cite
|
Sign up to set email alerts
|

Development and implementation of a three-choice serial reaction time task for zebrafish (Danio rerio)

Abstract: Zebrafish are an established and widely utilized developmental genetic model system, but limitations in developed behavioral assays have meant that their potential as a model in behavioral neuroscience has yet to be fully realized. Here, we describe the development of a novel operant behavioral assay to examine a variety of aspects of stimulus control in zebrafish using a 3 choice serial reaction time task (3 CSRTT). Fish were briefly exposed to three spatially distinct, but perceptually identical stimuli, pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 29 publications
2
46
0
Order By: Relevance
“…This test was performed as described previously (Parker et al, 2012). All behavioral testing took place in a custom-built tank.…”
Section: Zebrafish Behavioral Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…This test was performed as described previously (Parker et al, 2012). All behavioral testing took place in a custom-built tank.…”
Section: Zebrafish Behavioral Analysismentioning
confidence: 99%
“…per1b mutant fish display impulsivity-like phenotype Human ADHD patients show impulsivity and often have difficulty waiting for things they want. To investigate whether zebrafish per1b mutants show cognitive impulsivity, we performed a two-choice serial reaction-time task in adult fish as described previously (Parker et al, 2012), using a modified apparatus shown in Figure 1B. During 1-week-long consecutive daily training sessions, when a green light was accompanied by a food reward near the light, both the mutant and wild-type fish entered into the region near the green light within 1 min after it was switched on.…”
Section: Per1b Mutant Fish Display Hyperactive Behaviormentioning
confidence: 99%
“…Many vertebrate species lacking a well-developed neocortex nonetheless demonstrate clear behavioral signs of attention, including pigeons [52], peacocks [53], owls, [54], frogs [55,56], salamanders [57], and zebrafish [58]. For example, zebrafish can perform the same type of complex multi-choice serial reaction time task [59] that is commonly used to assess attention function in rodents [60]. …”
Section: Some Arguments In Favor Of This New Frameworkmentioning
confidence: 99%
“…The progress of the species in this respect is limited only by the rate at which laboratories develop and publish detailed behavioural protocols, such that any phyletic differences in learning capabilities or performance characteristics (qualitative or quantitative) can be scrutinised [3][4][5][6][7][8][9]. While quantitative differences in learning between vertebrate species are to be expected, qualitative differences in learning could severely compromise the translational relevance of animal models [10].…”
Section: Introductionmentioning
confidence: 99%